PENGARUH VIDEO ANIMASI BERBASIS ARTIFICAL INTELLIGENCE TERHADAP PENGETAHUAN REMAJA TENTANG DIET SEIMBANG PENCEGAHAN DIABETES MELITUS - Fitriani, Desi Nurul; Ruhmawati, Tati (Jurnal Kesehatan Siliwangi, 2024)
Background: Diabetes mellitus in children has increased by 8.5 percent. Most sufferers are over fifteen years old. The trend of eating junk food, which leads to obesity, and lack of physical activity, are usually responsible for the increasing incidence of type 2 diabetes in young people. The aim of this research is to increase students' knowledge at SMKN 1 Majalaya, Bandung Regency, about how to prevent type 2 diabetes. Method: This research uses a mixed design, step by step exploratory research (Mix Method Research). The proportional random sampling method was used to select research subjects, consisting of 51 students in class 11 of SMKN. The Wilxocon Signed Rank test was used to analyze data collected through interviews and questionnaires. Results: Research shows that students' knowledge scores increased by 33.73 before being given the media and by 93.14 after being given the media. Based on the analysis test, there is a significant knowledge value of 0.000, or 0.05. Conclusion: There is an influence of educational media via video on increasing students' knowledge about preventing type 2 diabetes at SMKN 1 Majalaya District. Bandung. Recommendation: Animated video educational media can be used as a medium in the learning process to increase students' knowledge regarding the prevention of diabetes mellitus.